An Exploratory Study of the Restricted-Use ELS:2002 Dataset: Using Finite Mixture Modeling as a Way to Problematize the Model Minority Stereotype (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Rather than review what the model minority stereotype is, or what the literature says about it, this article first reviews the methodologies that researchers and higher academicians have employed when conducting their scholarship on dispelling the model minority stereotype. The purpose of this empirical paper was to test whether the model minority in fact homogenizes Asian American socio-demographic realities. We sought to examine whether there were underlying subgroups of students who share similar demographic characteristics as Asian Americans. The researchers analyzed representative national data procured from the restricted-use Educational Longitudinal Study of 2002 (ELS:2002). This study is differently from other studies insofar as the researchers used finite mixture modeling (FMM) as a methodological approach to demystifying the model minority stereotype of Asian Americans. If the model minority stereotype of Asian Americans were true, then one might expect Asian American students to be members of the same latent class as their White counterparts. This pattern student membership was not only absent in the findings of this study, but the researchers found that class membership between Asian American students was the most varied out of the more prevalent minority groups represented in the data.